2017
DOI: 10.1021/acs.langmuir.7b01090
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Microscale Liquid Propagation in Micropillar Arrays

Abstract: Understanding the dynamics of microscale liquid propagation in micropillar arrays can lead to significant enhancement in macroscopic propagation modeling. Such a phenomenon is fairly complicated, and a fundamental understanding is lacking. The aim here is to estimate three main parameters in liquid propagation, capillary pressure, average liquid height, and contact angle on the pillar side, through modeling and experimental validation. We show that the capillary pressure is not constant during liquid propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The contact angle, θ CA , is an important parameter in the capillary flow [106]. Therefore, we measured θ CA as a function of temperature for both untreated and treated surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The contact angle, θ CA , is an important parameter in the capillary flow [106]. Therefore, we measured θ CA as a function of temperature for both untreated and treated surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the large mesh surface has the highest liquid propagation speed of 45 mm s −1 , which is around 1.8 times larger than the micropillar surface in our previous work. [ 45 ] We also evaluated their dryout heat fluxes, as shown in Figure 6c. It can be found that the large mesh surface has the best performance with a dryout heat flux of 26.3 W cm −2 , ten times larger than the optimized micropillar surface ( d = 42, p = 90, and h = 100 μm) in the study by Horner et al [ 46 ] Dividing the heat flux by water latent heat, we converted the dryout heat flux into the limit of vapor flux for vapor generation applications (see Figure 6c).…”
Section: Resultsmentioning
confidence: 99%
“…While substrates must be good thermal insulators with excellent water transporting properties. Therefore to be effective vapor generator, absorbers must have the following important properties: 1) absorb light across a wide range of wavelengths (380 to 2500 nm) and have a high-efficiency light-to-heat conversion; 2) capable of confining the generated heat to the evaporative surface for maximum evaporation and minimizing heat losses to the environment; and 3) the porous substrate should have good interface wettability and a well-designed structure for achieving continuous and efficient water transport form the underlying saline water reservoir to the upper evaporative surface [282,284]. However, achieving optimal outcomes for all these properties is challenging.…”
Section: Floating Solar Absorbers For Water Vapor Generationmentioning
confidence: 99%